Examined the relationship between Stellar Sea Lion diet diversity and population trends and characterized the spatial, temporal and seasonal variations in sea lion diet in the Aleutian Islands, Alaska, from 1990-2012 - Lowell Fritz (Research Workspace, 2019)
This collaborative study between the National Oceanic and Atmospheric Administration National Marine Fisheries Service, Sea Mammal Research Unit, and Fisheries and Oceans Canada investigated the relationship between diet and population trends of Steller sea lions in the Aleutian Islands. During this study, data from a total of 3,118 samples collected throughout the year in the Aleutian Islands from 1990-2012 (including 399 samples collected during this study at 14 sites (NPRB #1114: 345 in March 2012 and 54 in summer 2012) and 305 samples collected during NPRB #720) were analyzed to characterize the spatial, temporal and seasonal variation in sea lion diet and examined the relationship between population trend and diet diversity in both seasons and throughout the year. Additionally, a combination of dietary information methods, including traditional hard part identification and a molecular methodology developed by Tollit et al. (2009) that found DNA extracted from the soft scat of wild Steller sea lions, were used to sub-sample scat samples to identify prey occurrences that were undetected by hard parts alone. The data are stored in six csv files: NPRB_1114_Field_descriptions.csv, NPRB_1114_Species_names.csv NPRB_1114_Steller_sea_lion_hard_part_diet_data_species_list.csv NPRB_1114_Steller_sea_lion_hard_part_diet_data_sample_list.csv NPRB_1114_Steller_sea_lion_hard_part_diet_data_measured_otoliths.csv NPRB_1114_DNA_results.csv